MUSLIM JAWA : MASJID, KERATON DAN PASAR - Almunauwar Bin Rusli; Ishak Talibo (Institut Agama Islam Negeri (IAIN) Manado, 2020)
This article will look at how the perception of Javanese Muslims in Yogyakarta on Masjid, keraton, and market. This article employs a qualitative descriptive method with a sociological approach. Participatory observations, in-depth interviews, and literature studies were conducted at Malioboro. The result of the research shows that Javanese Muslims in Yogyakarta perceive the Muttaqin Mosque as a moral-spiritual symbol, the Keraton Yogyakarta as a cultural-political symbol and the Beringharjo market as a socio-economic symbol. In summary, Javanese Muslim perceptions above are constructed by five factors that: Alon-alon waton kelakon, nrimo ing pandum, sepi ing pamrih rame ing gawe banter tan mbancengi dhuwur tan ngungkuli, mangan ora mangan asal ngumpul and tuna satak, bathi sanak.Keywords: Javanese Muslim; Masjid; Keraton; MarketPenelitian ini akan melihat bagaimana persepsi Muslim Jawa di Yogyakarta tentang masjid, keraton dan pasar. Penelitian ini menggunakan metode deskriptif kualitatif dengan pendekatan sosiologis. Pengamatan partisipatif, wawancara mendalam dan studi literatur dilakukan di Malioboro. Hasil penelitian menunjukkan bahwa Muslim Jawa di Yogyakarta mempersepsikan Masjid Muttaqin sebagai simbol moral-spiritual, Keraton Yogyakarta sebagai simbol budaya-politik dan pasar Beringharjo sebagai simbol sosial-ekonomi. Kesimpulannya, persepsi Muslim Jawa di atas dikonstruksi oleh lima faktor yaitu alon-alon waton kelakon, nrimo ing pandum, sepi ing pamrih naik gawe banter tan mbancengi dhuwur tan ngungkuli, mangan ora mangan asal ngumpul dan tuna satak, bathi sanak Kata Kunci: Muslim Jawa; Masjid; Keraton; Pasar